Tale of the Frail: Understanding Frailty in Cirrhosis. Issue 3 (March 2021) - Pradhan, Faruq; Narang, Natasha; Fallon, Michael
Abstract : Frailty is a dynamic biologic syndrome that has been recognized increasingly as an important factor in healthcare resource utilization and costs. Evaluating frailty has becoming particularly relevant in cirrhosis because it is noted to be a useful predictor of outcomes both before and after liver transplantation. This review examines the importance of considering frailty in cirrhosis, as well as methods for assessing and managing frailty in patients with chronic liver disease. Care for cirrhosis patients is anticipated to increasingly shift to multidisciplinary care involving internists and primary care providers alongside hepatologists because of the projected upsurge in the prevalence of end-stage liver disease. Recognition of risk factors for frailty and early diagnosis will enable medical providers to improve comprehensive care for patients with cirrhosis. Abstract: Frailty is a dynamic condition that results in increased vulnerability to health stressors. Often associated with older adults, frailty is not limited to the geriatric population, although aging and disease burden often go hand in hand. This syndrome is recognized increasingly as an important factor in healthcare costs, rate of adverse outcomes, and overall resource utilization. Frailty may be reversible to a degree, and thus appropriate recognition affords a focus for efficient intervention. Notably, frailty is becoming increasingly relevant in cirrhosis, and has been noted to be an independent predictor of outcomes in patients both before and after liver transplantation. Cirrhosis is currently the 12th leading cause of death in the United States, and its incidence is anticipated to markedly increase in the coming years with the aging of our population. With the anticipated surge in disease prevalence, liver disease care will likely shift from specialist-driven to a multidisciplinary approach between primary care physicians, internists, and hepatologists to adequately care for these patients. This review serves as a guide for clinicians to learn about frailty, its role in cirrhosis, and the current tools to educate patients and families about the importance of nutrition and physical exercise within this population.